Analysis of chef works’ master budget to minimize the value of leftover product - Wiguna, Giovanni Julius; Darmansyah, Asep (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. Culinary business is one of the fastest growing business in Indonesia. According to Badan Ekonomi Kreatif Indonesia or BEKRAF, culinary as one of creative economy sub-sector is in the top of sub-sector that has the most number of businesses. Chef Works is one of business that runs in food and beverages industry and located in Bandung. Right now, Chef Works focuses on making packaged filling bread with “modern” fillings. As a new established company, finance is become one of the most important factor to grow the business. Based on 2018 financial data, Chef Works has leftover products and ingredients or waste expense worth approximately 1.6 million rupiah in a year. The issue is related to the inaccurate of budgeting process in the first place. By using fishbone analysis, it is known that the company did inaccurate in making budgeting process especially in sales budget when the company should determine sales target unit forecast. To minimize the value of leftover product, the company should create a “right” initial budgeting. To create the most suitable budgeting for the company, company should consider factors that can affect company in determining the budgeted sales or sales forecast such as customer preference. After considering several factors, then the researcher creates a new master budget for the company. But the company needs other aspect/unit support especially marketing to run the budgeting plan. It is ineffective if the marketing unit does not make any moves to support the sales.Keywords: leftover products, inaccurate, budgeting, sales forecast